Heavy metals in wastewater and fish collected from waste stabilization pond and human health risks in southwestern Ethiopia - Berhanu, Girma; Lemma, Hailu; Mekonnen, Seblework; Dadi, Dessalegn (Frontiers in Environmental Health, 2024)
Introduction This study aimed to measure the concentration of toxic heavy metals in wastewater samples and Nile tilapia (Oreochromis niloticus) species inhabiting wastewater (waste stabilization ponds) and evaluate their safety as a food source in southwestern Ethiopia. For this purpose, toxic metals like lead (Pb), cadmium (Cd), arsenic (As), and mercury (Hg) in wastewater samples and fish tissues (muscle, gill, and liver) were independently examined. Methods A laboratory-based cross-sectional study was performed to ascertain the levels of Pb, Cd, As, and Hg in the fish tissues of O. niloticus and wastewater samples. Heavy metal levels were analyzed by microplasma atomic emission spectrometry (Agilent 4210 MP-AES) and hydrogen-generated atomic absorption spectrometry (HGAAS, novAA 400P, Germany). Results Heavy metal concentrations were measured in the following decreasing order (µg L−1): Cd > Pb > As > Hg in facultative and maturation ponds, with Cd (27.66 µg L−1) having the highest concentration and Hg (0.349 µg L−1) having the lowest concentration. Among the heavy metals detected in the wastewater samples, Hg showed a statistically significant difference between the sampling points (p = 0.023). The maximum metal concentration was measured for Pb (0.35 mg kg−1) and Cd (0.24 mg kg−1) in the muscle tissue of O. niloticus. The value of arsenic (0.02 mg kg−1) detected in fish edible muscles exceeded the FAO/WHO maximum permissible limit (MPL = 0.01) for human consumption. The carcinogenic and non-carcinogenic health risks of consuming fish due to trace metals were relatively low and posed fewer potential threats to human health. According to this finding, children were more susceptible to heavy metal exposure than adults. Conclusion Due to the high quantities of these harmful heavy metals, wastewater from oxidation ponds should not be used for fishing to avoid bioaccumulation. The target carcinogenic risk (TR) and target hazard quotient (THQ) indicated that all heavy metals were below the safe threshold. This research will provide a baseline for monitoring trace metals in various edible aquatic creatures and for future research in artificial habitats and regulatory considerations.